Ultrastructural morphometry of neurosecretory granules in neuroblastomas of pediatric patients - Jovanović, Sofija D; Kravić-Stevović, Tamara (Medicinski podmladak, 2018)
Introduction: Peripheral neuroblastic tumours are among the most frequently detected tumours in paediatric patients. A correlation between the aggressiveness of these tumours and their clinical prognosis has been discovered. Neurosecretory granules containing neurotransmitters, an ultrastructural feature of neurons, were found in the cells of peripheral neuroblastic tumours, as well. Aim: The aim of this study was to compare the number of neurosecretory granules found in cells of tumours with a favourable prognosis to the corresponding number in cells of tumours with an unfavourable one with the use of transmission electron microscopy (TEM). Material and Methods: Ten tissue biopsies were obtained from paediatric patients diagnosed with peripheral neuroblastic tumours. The tumour samples were first frozen, then fixed in glutaraldehyde, and embedded in epoxy resin. Ultrastructural morphometric analysis was performed on ultrathin sections. Results: It was found that the cells of tumours with an unfavourable prognosis have more neurosecretory granules in their cytoplasm than the cells of tumours with a favourable one. Conclusion: The larger number of neurosecretory granules found in cells of tumours with an unfavourable prognosis could potentially shed some light on the role these structures play in tumourigenesis. Key words: neurosecretory granules, peripheral neuroblastic tumours, prognosis, ultrastructural morphometry